Effectiveness of Different Chemotherapeutic Agents for Decontamination of Infected Dental Implant Surface: A Systematic Review - Chayya Patil; Amit Agrawal; Shahabe Saquib Abullais; Suraj Arora; Shafait Ullah Khateeb; Mohamed Fadul A. Elagib (Antibiotics, 2022)
Aim: To evaluate the most effective chemotherapeutic agent for decontamination of infected dental implants. Material and methods: A systematic electronic literature search in MEDLINE (PubMed) and Google scholar between January 2010 to December 2021 was carried out by using the PRISMA guidelines. A total of five studies related to chemical decontamination of the dental implant were evaluated. The search strategy was based on the PICOS framework. Randomized controlled trials (RCT’s) and cohort studies evaluating the effectiveness of different chemotherapeutic agents for the decontamination of dental implants were included in the study. The outcome variable examined was the most effective chemotherapeutic agent(s) for dental implant surface decontamination after comparing the chemotherapeutic agents used in the qualifying studies. Result: Out of the basic database of 1564 records, 1380 articles were excluded due to irrelevance, unavailability, and repetition. Furthermore, 134 articles were excluded from 184 studies for various reasons. After further filtration, 13 studies were shortlisted. Two investigators (SSA and SA) appraised the quality of the selected studies using the risk of bias assessment tool. After excluding eight studies, five articles were finally included in the present systematic review. Conclusion: The data reported for the efficacy of chemotherapeutic agents in cleaning contaminated titanium surfaces are scarce, thus it is not possible to draw a definite conclusion. However, chlorhexidine (CHX) (0.2%, 0.12%), citric acid (40%) and sodium hypochlorite (1%) are the most commonly used chemotherapeutic agents; amongst them, citric acid showed the highest potential for biofilm removal from the contaminated implant surface. All three agents [CHX (0.2%, 0.12%), citric acid (40%), and sodium hypochlorite (1%)] can be recommended as therapeutic agents along with their curbs.